2004
DOI: 10.1159/000077011
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Soluble Antioxidants and Pregnancy: Maternal Serum Levels of Coenzyme Q<sub>10</sub>, α-Tocopherol and γ-Tocopherol in Preeclampsia and Normal Pregnancy

Abstract: It has been hypothesized that in preeclampsia, the antioxidant-deficient state may facilitate increased attacks of free radicals, which may result in endothelial cell damage. The purpose of this study was to investigate the association of three lipid-soluble antioxidants, coenzyme Q10, α-tocopherol and γ-tocopherol, with preeclampsia and normal pregnancy. Serum levels of all three antioxidants in 42 women with normal pregnancies, 25 with mild preeclampsia and 28 with severe preeclampsia were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
2
18
0
4
Order By: Relevance
“…This finding is in agreement with a previous work that showed that a-tocopherol enhances the vitality of nerve cells [3]. Furthermore, a-tocopherol functions as a cofactor in the manufacture of crucial fatty acids, and plays a part in the synthesis of neurotransmitters that include 5-hydroxytryptamine, dopamine, noradrenaline, and gamma-aminobutyric acid (GABA); GABA contributes to the normal performance of the nervous system [5,35].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with a previous work that showed that a-tocopherol enhances the vitality of nerve cells [3]. Furthermore, a-tocopherol functions as a cofactor in the manufacture of crucial fatty acids, and plays a part in the synthesis of neurotransmitters that include 5-hydroxytryptamine, dopamine, noradrenaline, and gamma-aminobutyric acid (GABA); GABA contributes to the normal performance of the nervous system [5,35].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, biopyrrin was adopted as a marker for oxidative stress because it is a predictor of optimal lifestyle during pregnancy. Furthermore, the antioxidant CoQ10 was used to clarify the relationship between oxidative stress and pregnancy complications in previous studies (1,3). In addition, CoQ10 has a strong antioxidant effect on the human body; hence, it was considered as a marker for oxidative stress.…”
Section: Participantsmentioning
confidence: 99%
“…* : p < 0.05, ** : p < 0.01, *** : p < 0.001 by multiple regression analysis. 1) n = 52 in the second trimester with missing data for biopyrrin level and the GHQ.…”
Section: Relationship Between Oxidative Stress Antioxidants and Lifmentioning
confidence: 99%
See 2 more Smart Citations